Use of solid plastic waste PET for the construction of an ecological habitation in Tacna - Tirado Rebaza, Leo Ulises Michaell (2021)
What prompted me to carry out this investigation was the problem generated by solid plastic waste in the heroic city. This research had as objectives: (1) take advantage of the PET plastic solid waste to build an ecological room in Tacna, (2) determine the interior and exterior temperature of the building and (3) identify the advantages and disadvantages of ecological construction vs. a traditional construction. The ecological room had dimensions of 4.5 m x 3.5 m x 2.0 m and 3 200 plastic PET bottles compacted with soil were necessary for its construction. To prepare the complementary mixture used in the building, water, clay, farmland and dry Cynodon dactylon were used, in proportions of 6, 5, 4 and 0.05, respectively. The construction was carried out by forming layers composed of the mentioned polymer and the mixture. The roof of the eco-infrastructure was made up of corbels and wooden beams. It was evident that an ecological room can only be used as a home due to the comfortable environment inside. It was proven that the building can be carried out safely, economically and peacefully with the environment.